Le Martyre BHG 2109 et les Passions BHL 2264-2265 de Donnino le céphalophore de Fidenza - Lequeux, Xavier (Analecta Bollandiana, 2004)
The Greek Martyrium of St Domninus (BHG 2109) is an anonymous translation of a lost recension of the early Passion of the patron saint of Fidenza (BHL 2264 and 2265). This local history, which also inspired Odo of Beauvais († 881) in his compilation of the Passion of St Lucian (BHL 5009), was probably written in the early ninth century. The Greek Martyrium, which has survived in one Italo-Greek witness (MS Ambrosianus F 144 sup., 10/11th cent., ff. 116r-117v), as well as the editio princeps of the Passio S. Domnini (BHL 2265) on the basis of MS Boll. 162, ff. 38r-39v of which were copied from MS Barberinus Lat. 586 (10/11th cent., ff. 279-280), have been reedited in an appendix.